Shia and Sufi Mystical Interpretation of Systematic Integration from Seyyed Heydar Amoli’s Perspective - Esfahani, Seiyed Abdullah; Hosseini, Seyyede Masoome (Journal of History Culture and Art Research, 2017)
A knowledge of the mechanism behind Shia and Sunni mystical interpretation of systematic integration, something from a learned commentator such as Allameh Seyyed Heydar Amoli, making the due efforts for reconciliation between the true Sufi and mystic and real Shiite…and linking the sacred law (Sharia), Sufi path and the truth, possesses the theoretical Quranic necessity. The present research implements descriptive and analytical methodology to understand his interpretation known as "Al-Moheit Al-Aazam" and other writings. Amoli believes the literal meaning of the expressions in perceiving the macrocosm and microcosm realities through the discovery of Quranic teachings and teachings of these three books, acquired the knowledge of God and Divine Names and Attributes using the tools of Qur’an, demonstration and mysticism. The systematic integration he has in mind has been somehow reflected in the views of the great famous scholars such as Imam Khomeini, Allame Tabatabaee, Ayatollah Javadi Amoli, and Ayatollah Hassan-zade Amoli. Undoubtedly, such attitude clarifies the connection and continuity between various worlds and levels of being and the issue, i.e., the mystical interpretation of Qur’an will get more valuable and a more charming status.